Rent sharing and gender discrimination in collegiate athletics - Mario Lackner; Christine Zulehner (Johannes Kepler University of Linz, Department of Economics, 2013)
In this paper, we analyze the effect of market power on the share of females in top management positions using data from a market in which some firms have market power due to an institutionalized cartel. We investigate collegiate athletics and interpret coaches as top-level managers or chief executive officers (CEOs).The causal link between market power and female employment is established by exploiting the existence of the Bowl Championship Series (BCS) as an exogenous shock. Our results show that an increase in the market share has a negative effect on females relative to males among coaches. We interpret this as clear evidence for Becker's (1957) theory on employer discrimination. Only firms operating in an oligopolistic or otherwise not perfectly competitive environment can sustain a taste or cost of discrimination. Market power is necessary to let firms share rents with their workers, which they do in a discriminatory way.
Keywords: J71; L40; 330; gender discrimination; market power; Ballsport; Ausbilder; Weibliche Führungskräfte; Marktmacht; Geschlechterdiskriminierung; USA